Azole-resistant invasive aspergillosis in a patient with acute myeloid leukaemia in Germany - Hamprecht, Axel; Buchheidt, Dieter; Spiess, Birgit (Eurosurveillance, 2012)
We report the first culture-proven case of invasive aspergillosis (IA) caused by azole-resistant Aspergillus fumigatus in a patient with acute myeloid leukaemia in Germany. IA presented as breakthrough infection under posaconazole prophylaxis. Analysis of the resistance mechanism revealed the TR/L98H mutation in the cyp51A gene, which indicates an environmental origin of the strain. This case underscores the need for monitoring azole resistance in Aspergillus spp. and for routine susceptibility testing of moulds.